Characterization of partially purified Î²-galactosidase from Bacillus Sp MTCC-864 - A. S. Bawa, M. M. Patil*, Mallesha, K. V. Ramana and (Recent Research in Science and Technology, 2011)
Î²-Galactosidase is an important enzyme for the hydrolysis of lactose in milk and other by-products of dairy industry such as whey and for the synthesis of galacto-oligosaccharides known for their prebiotic properties. In the present study we report the extraction, partial purification and characterization of intracellular Î²-galactosidase from Bacillus sp MTCC-864. The media containing tryptone, yeast extract and lactose was used for growth and enzyme production. The enzyme was extracted through ammonium sulphate fractionation and gel permeation chromatography technique using Sephacryl-200. Optimum enzyme activity was found at 50oC and pH 7.0. Further enzyme activity was enhanced in the presence of divalent metal ions such as Mg++ and Mn++, while it was inhibited by EDTA. The enzyme was thermostable and retained 70% of its original activity after 30min of incubation at 60oC. These properties of enzyme indicate its potential use for hydrolysis of lactose in milk and whey from the dairy industry.